1976
DOI: 10.1080/00039896.1976.10667211
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Selenium Distribution in a Defined Area and in Its Population

Abstract: In the Amiata Mountain area of Tuscany, Italy, a survey has examined the concentrations of mercury and selenium in the environment, in the food chain, and in human biological samples of blood, urine, and hair. This area was selected for study because of its large mineral deposits and concentration of elements, e.g., iron, copper, silver, antimony, and particularly mercury. Subjects consisted of a group with high occupational exposure to mercury vapor, a group randomly exposed to mercury dust, and a group nonoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Kazantzis et al [13] found Hg concentrations of 25 and 10 lg/g, respectively, in kidney biopsies from two workers suering from nephrotic syndrome. At the time of biopsy they had been unexposed for about 2 months and excreted 300±400 lg Hg/24 h. Rossi et al [19] found concentrations of 0.2 and 2.8 lg/g in two miners, but their level of exposure had been very low. BoÈ rjesson et al [1] reported the results of in vivo XRF measurements of kidney-Hg in 20 Hg-exposed chloralkali and thermometer workers.…”
Section: Kidney-hgmentioning
confidence: 94%
See 1 more Smart Citation
“…Kazantzis et al [13] found Hg concentrations of 25 and 10 lg/g, respectively, in kidney biopsies from two workers suering from nephrotic syndrome. At the time of biopsy they had been unexposed for about 2 months and excreted 300±400 lg Hg/24 h. Rossi et al [19] found concentrations of 0.2 and 2.8 lg/g in two miners, but their level of exposure had been very low. BoÈ rjesson et al [1] reported the results of in vivo XRF measurements of kidney-Hg in 20 Hg-exposed chloralkali and thermometer workers.…”
Section: Kidney-hgmentioning
confidence: 94%
“…However, by 1993, when these two workers were studied, the work environment had improved. In deceased mercury miners who had been retired for several years the concentration of mercury measured in autopsy kidneys ranged from 2 to 19 lg/g [14,19]. Hargreaves et al [10] reported kidney-Hg levels of 1.7± 2.6 lg/g at the autopsy of a thermometer worker with a high level of prior Hg exposure (18 months, clinical symptoms of intoxication, U-Hg 700 lg/24 h, B-Hg 480 lg/l) that had ended 16 years previously.…”
Section: Kidney-hgmentioning
confidence: 99%
“…(Khan et al 1996;Bachman et al 2002;Anne et al 2007;Mohammad et al 2010). Most heavy metals tend to be associated with sulphar in protein (Rossi and Santaroni 1976). The heavy metals content of streams, lakes and rivers did not normally exceed 0.1 ppm although some water sources located near different heavy metals deposits might contain mixed amounts up to 80 ppm (Wershow 1970;Bachman et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably high levels of mercury in brain from persons with high levels of exposure in early life followed by a long time of no exposure and no obvious neurological signs have been reported by several authors (13,14). The close correlation between mercury and selenium content in the brain found by two authors (12,15), and the remarkably long retention time of mercury in the brain indicate an association between selenium and mercury storage in the human central nervous system.…”
Section: Selenium Interaction With Elemental Mercury Toxicity and Metmentioning
confidence: 89%